Interactional dynamics in remote interpreting : micro-analytical approaches - De Boe, Esther, 1971-; Vranjes, Jelena; Salaets, Heidi (New York, NY : Routledge, 2024)
"This collection introduces an innovative micro-analytical approach to interaction management in remote interpreting, offering new insights into our understanding of the conversational dynamics of remote dialogue interpreting. The book calls attention to the need for greater reflection on the impact of the increased use of remote interpreting via telephone and video link, particularly in light of the COVID-19 pandemic, on the already complex interactional dynamics of communication in dialogue interpreting settings. Featuring perspectives from both established and emerging scholars, the volume explores both the signals and mechanisms of interaction management and the effects of context in such settings. Chapters draw on empirical studies based on experimental and authentic data from video recordings and eye-tracking data to examine the impact on smoothness and synchronization of the interaction in remote interpreting, in light of the absence of multimodal resources such as gaze and gesture. In collecting this research in a single volume, the book paves the way for further research on the changing relationships between interaction management, technology, and multimodality in dialogue interpreting contexts in today's increasingly technology-mediated world. This volume will be of interest to students and scholars in interpreting studies, language and communication, and pragmatics"--
Keywords: Interactive management; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics